Guideline adherence and socioeconomic factors in Danish patients referred to secondary care for low back pain: a cross sectional study - Lise Hestbæk; Anne Mette Schmidt; Majbrit Andsbjerg Hald; Nanna Rolving (BMC, 2023)
Abstract Background The pre-referral history of patients with low back pain referred to secondary care is poorly documented, and it is unclear whether it complies with clinical guideline recommendations; specifically, whether they have received appropriate treatment in primary care. This study describes the patient population referred to a spine clinic at a Danish hospital and investigates whether they have received an adequate course of treatment in primary care before referral. Furthermore, a possible association between primary care treatment and socioeconomic factors is estimated. Methods We examined self-reported data from 1035 patients with low back pain of at least eight weeks duration referred to secondary care at a medical spine clinic using a cross-sectional design. As an approximation to national clinical guidelines, the definition of an adequate course of treatment in primary care was at least five visits to a physiotherapist or chiropractor prior to referral. Results Patients were on average 53 years old, and 56% were women. The average Oswestry Disability Index score was 36, indicating a moderate level of disability. Nearly half of the patients reported pain for over a year, and 75% reported pain below knee level. Prior to referral, 33% of the patients had not received an adequate course of treatment in primary care. Based on multiple logistic regression with the three socioeconomic variables, age and sex in the model, those who were unemployed had an odds ratio of 2.35 (1.15-4.79) for not receiving appropriate treatment compared to employed patients. Similarly, the odds ratio for patients without vs. with health insurance was 1.71 (1.17-2.50). No significant association was observed with length of education. Conclusions Despite national clinical guidelines recommending management for low back pain in primary care, one third of the patients had not received an adequate course of treatment before referral to secondary care. Moreover, the high probability of not having received recommended treatment for patients who were unemployed or lacked health insurance indicates an economic obstacle to adequate care. Therefore, reconsidering the compensation structure for the treatment of back pain patients is imperative to mitigate health inequality within low back pain management.